Sosyal medya'da performatif öznellik : Instagram'da hijabista paylaşımları - Ünver, Hande Akyıl (My University, 2023)
Yeni iletişim teknolojileri sadece toplumsal ve ekonomik yaşamda değil; bireylerde de hızlı değişimlere yol açmıştır. Sosyal Medya özellikle de görüntü tabanlı platform olan Instagram, bireyler ve özellikle de kadınlar için kendilerini göstermek ve öznellik oluşturmak için yeni bir mecra ve bir alan olmuştur. Postfeminizm, hak mücadelesinden çok çağdaş popüler kültür ve medya formlarıyla gelişmiş bir kültürdür. Bu çalışmada Instagram’daki Hijabista profil, paylaşım ve selfie’leri eleştirel ve olumlayıcı iki yaklaşımla yorumlanarak, postfeminist kültür unsurlarıyla birlikte incelenecektir. Postfeminist kültürün kadın öznellikleri üzerine olan etkileri tartışılacak, paylaşımlar performatif toplumsal cinsiyet çerçevesinde değerlendirilerek cinsiyete dayalı öznellikler yaratmak için Instagram’da kullanılan söylemsel ve performatif tarz ile ortaya çıkan öznellikler tartışılacaktır. Postfeminist kültürün kadınların hayatına farklı bir şekilde getirdiği güçlenme, tüketimcilik, kendine güven ve kişisel gelişim unsurları, ilişkilere sızan neoliberal kültür, Instagram’daki içerik ve ayrıca gerçekleştirilen mülakatlar üzerinden çözümlenmeye çalışılacaktır.

As new communication technologies and digital technology have led to rapid changes in individuals, not only in social and economic life but also in cultural and affective life. Women have a new area to express themselves nowadays. They have a new sphere to express their individual preferences and identities/ subjectivities in New Media especially on Instagram which is an image-based platform. Feminism has defined the struggles that have lasted for years, mostly through political action, for the purpose of gender equality, while postfeminism is a culture that has mostly developed with contemporary popular culture and media forms. The empowerment, consumerism, self-confidence and self-improvement that women bring to their lives once again and in a different way in a neoliberal culture infiltrating relationships will be analyzed through content on social media and interviews. In this study, the Hijabista profiles, posts and selfies on Instagram will be analyzed with postfeminist cultural elements and sensibility, and the effects of postfeminist culture on female subjectivities will be discussed by interpreting them with both critical and affirmative approaches.
Performative subjectivities on social Media : Hi̇jabi̇sta posts on Instagram
Keywords: Instagram; Öznellik; Performatif Cinsiyet Social media; Performative Gender; Postfeminism; Postfeminizm; Social media; Sosyal medya; Subjectivity